2014
DOI: 10.1542/peds.2014-0537
|View full text |Cite
|
Sign up to set email alerts
|

Cyber Dating Abuse Among Teens Using School-Based Health Centers

Abstract: WHAT'S KNOWN ON THIS SUBJECT: Cyber dating abuse victimization has been correlated with physical, sexual, and psychological adolescent relationship abuse. WHAT THIS STUDY ADDS:This is the first clinic-based study of cyber dating abuse. Forty-one percent of youth reported cyber dating abuse victimization, female more than male respondents. Compared with nonexposed youth, abuse victims reported more sexual assault; female victims reported more contraceptive nonuse and reproductive coercion. abstract OBJECTIVE: T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
117
3
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 113 publications
(136 citation statements)
references
References 31 publications
5
117
3
8
Order By: Relevance
“…The intervention is universal, inclusive of all genders, sexual orientation, and clinic visit types, addressing a range of abusive behaviors, including cyber dating abuse (the use of social media to abuse a partner). 19,20 This study uses a cluster randomized controlled trial (RCT) design to evaluate the effectiveness of this brief universal education and counseling intervention to improve adolescents' recognition of ARA, use of resources, and attitudes and behaviors to reduce ARA. The study's 3 prespecified primary outcomes for the full sample focused on ARA knowledge and attitudes: (1) recognition of abusive behaviors, (2) intentions to intervene, and (3) knowledge of ARA resources.…”
Section: What This Study Addsmentioning
confidence: 99%
“…The intervention is universal, inclusive of all genders, sexual orientation, and clinic visit types, addressing a range of abusive behaviors, including cyber dating abuse (the use of social media to abuse a partner). 19,20 This study uses a cluster randomized controlled trial (RCT) design to evaluate the effectiveness of this brief universal education and counseling intervention to improve adolescents' recognition of ARA, use of resources, and attitudes and behaviors to reduce ARA. The study's 3 prespecified primary outcomes for the full sample focused on ARA knowledge and attitudes: (1) recognition of abusive behaviors, (2) intentions to intervene, and (3) knowledge of ARA resources.…”
Section: What This Study Addsmentioning
confidence: 99%
“…Most research focuses on the problematic side of online dating, such as the risk of dating violence and the risk of being sexually abused (Dick et al, 2014). However, research shows that sexual communication in text or through pictures or films is often seen as part of dating behaviour (e.g.…”
Section: Online Dating For Romantic or Sexual Relationshipsmentioning
confidence: 99%
“…Sending sexual images to a partner can be done after feeling pressured to do so (Associated Press & MTV, 2009;Handerson & Morgan, 2011). In a study by Dick et al (2014), cyber dating abuse among youth (14-19 year olds) who had soughed care at school-based health centres were investigated. In the study 13% reported sexual cyber dating abuse.…”
Section: Negative Consequences Of Online Sexual Behavioursmentioning
confidence: 99%
“…Similarly, Zweig et al (2013) found that females perpetrated more non-sexual cyber dating abuse than did males. Dick et al (2014) noted that females also reported more cyber dating abuse victimization than males. However, when it comes to sexual dating abuse, both traditional and cyber, males report as much as twice the amount of female perpetration (Foshee, 1996;Zweig et al, 2013).…”
Section: Introductionmentioning
confidence: 98%